A delayed foreskin-sparing approach to the management of penile fractures in uncircumcised Jamaican men. (2015) - Wong, Dean P.; Morrison, Belinda F.; Mayhew, Richard G.; Reid, Gareth A.; Aiken, William D.
Highlights: Suitable for uncircumcised men with a penile fracture without urethral injury. An intentional delay of seven days is made before reassessment of the patient. In true penile fractures a "rolling sign" at the fracture site is felt at day seven. Focal incision over the fracture site under local anaesthesia is possible. The delayed approach mitigates against negative surgical exploration. Abstract: Introduction: The traditional surgical approach to penile fracture is to perform a circumferential subcoronal degloving incision emergently to repair the injury. This approach necessitates circumcision to avoid foreskin complications. We present four men who had a delayed foreskin-sparing approach and discuss its advantages. Presentation of case: Four of five uncircumcised patients who had suspected penile fractures secondary to coital injury, and without suspicion of concomitant urethral injury, had a delayed exploration, seven days after injury, utilizing an incision directly over the palpable haematoma, at the location of the tunical defect, thereby resulting in foreskin preservation. Two of 5 patients had repair under general anaesthesia, one under local anaesthesia and surgery was cancelled in another because upon reassessment at seven days he had normal erections and a normal penile examination. At follow up, all men had good functional and cosmetic outcomes. Discussion: Uncircumcised patients with penile fractures, without suspicion of urethral injury, may undergo a delayed repair without prophylactic circumcision since there is minimal risk of foreskin complications. Delayed repair decreases the incidence of negative explorations by fostering a conservative approach in mimicking conditions such as superficial vein lacerations. It also enables the use of local anaesthesia in an elective ambulatory setting. Conclusion: Delayed repair of penile fractures results in foreskin preservation, facilitates elective ambulatory care under local anaesthesia and decreases the incidence of negative surgical explorations.